Evaluation of the dietary outcomes among middle-aged Libyan edentulous male subjects treated with complete dentures; Part 1: The perceived ability to chew. - Burawi, Gamal G.; El huni, Rabie M.; Lefsaay, Amel M.; Elnaihoum, Warida A.; Mohammed, Isaeida A.; Ali, Faraj A. (Libyan Journal of Science &Technology, 2025)
Statement of problem: The implant-retained or supported overdentures have been indicated as the primary treatment of edentulousness. However, for obvious reasons fewer patients will afford this type of treatment. Therefore, it is desirable to investigate and re-establish the effectiveness of the provision of complete dentures on patients’ essential oral functions. Aim of the study: To assess the perceived chewing ability of edentulous Libyan patients rehabilitated with traditional complete dentures. Materials and methods: Thirty-five edentulous adult male patients were carefully selected for this clinical trial. The researchers interviewed all subjects and assisted them in filling accurately the visual analogue scale questionnaire (VAS). The VAS questionnaire contained efficiency-rating questions assessing the effectiveness of wearing complete dentures on the ability to chew seven locally favourite meals. The answer for each question was ranked from zero to 100. Then, a standard treatment procedure was performed to provide each subject with a conventional complete denture. At the recall visit scheduled after six months of post-insertion of all prostheses, the same researchers helped subjects to indicate again their satisfaction level with their complete dentures using the same practice VAS questionnaire. The VAS scores recorded pre-treatment were compared to those scores recorded post-treatment using Wilcoxon signed-rank tests. Results: All subjects verbally expressed their contentment and enjoyment when eating meals using their dentures. The perceived ability to chew was significantly improved for almost all food tested except for those, which require slicing before chewing. The conventional complete dentures still provide edentulous patients with an improved chewing ability when consuming traditional Libyan meals. Conclusion: An optimistic improvement of chewing ability with complete dentures is achieved as shown by the validated practice VAS questionnaire. Consequently, the treatment with traditional complete dentures can be generalized and used for wider edentulous patients seeking treatment in the Libyan general dental practice.